2021
DOI: 10.1136/gutjnl-2020-321031
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng polysaccharides alter the gut microbiota and kynurenine/tryptophan ratio, potentiating the antitumour effect of antiprogrammed cell death 1/programmed cell death ligand 1 (anti-PD-1/PD-L1) immunotherapy

Abstract: ObjectiveProgrammed death 1 and its ligand 1 (PD-1/PD-L1) immunotherapy is promising for late-stage lung cancer treatment, however, the response rate needs to be improved. Gut microbiota plays a crucial role in immunotherapy sensitisation and Panax ginseng has been shown to possess immunomodulatory potential. In this study, we aimed to investigate whether the combination treatment of ginseng polysaccharides (GPs) and αPD-1 monoclonal antibody (mAb) could sensitise the response by modulating gut microbiota.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(169 citation statements)
references
References 56 publications
4
164
0
1
Order By: Relevance
“…Metabolism plays an important role in carcinogenesis, and in recent years, it has been leveraged for tumor treatments (Biswas, 2015;Vander Heiden and DeBerardinis, 2017;Kumar and Misra, 2019). Multiple studies have shown that metabolism and cancer are closely related; currently, metabolites are important targets in the treatment of cancer (Chae and Kim, 2018;Dinges et al, 2019;Huang et al, 2021). The mitochondria electron transport chain locates in the inner membrane of the mitochondria and is composed of four complexes, including complexes I, II, III, and ATP synthase (Chen and Butow, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism plays an important role in carcinogenesis, and in recent years, it has been leveraged for tumor treatments (Biswas, 2015;Vander Heiden and DeBerardinis, 2017;Kumar and Misra, 2019). Multiple studies have shown that metabolism and cancer are closely related; currently, metabolites are important targets in the treatment of cancer (Chae and Kim, 2018;Dinges et al, 2019;Huang et al, 2021). The mitochondria electron transport chain locates in the inner membrane of the mitochondria and is composed of four complexes, including complexes I, II, III, and ATP synthase (Chen and Butow, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Korean ginseng, a root of Panax ginseng C.A. Meyer, contains various biologically active components such as ginsenosides, polysaccharides, and glycolipoproteins [1,9,10]. In a previous study, we isolated a glycolipoprotein called gintonin from ginseng and found that gintonin has a variety of components including ginseng major latex-like protein151 (GLP151), ginseng ribonuclease-like storage protein, phosphatidic acids, and lysophosphatidic acid (LPA) [11].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to cancer, a recent study showed that oral ginseng polysaccharides combined with anti-PD-1-mAb could improve therapeutic sensitivity of anti-PD-1-mAb in patients with NSCLC. This effect may have been related to ginseng polysaccharides-induced remodeling of gut microbiota structure in chemotherapeutic non-responders that led to increased abundance of metabolites, such as short-chain fatty acids (SCFAs), while also down-regulating IDO activity ( Huang et al, 2021 ). Thus, the immunosuppressive TME associated with NSCLC was altered, leading to heightened immunotherapeutic sensitivity induced by ginseng polysaccharides administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ginseng polysaccharides enhanced the anti-tumor response triggered by anti-PD-1 mAb by increasing CD8 + T cell function and decreasing Treg inhibition. These effects may have been due to effects of ginseng polysaccharides on tryptophan metabolism that acted to reshape the gut microbiota that resulted in significantly increased production of L-tryptophan and decreased production of L-kynurenine and IDO expression in tumor cells ( Huang et al, 2021 ). In conclusion, ginsenosides and ginseng polysaccharides appear to enhance the adaptive immune response against tumor cells, warranting further study ( Figure 2 ).…”
Section: Ginseng May Regulate the Tumor Immunosuppressive Microenvironmentmentioning
confidence: 99%